2006
DOI: 10.1063/1.2424280
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of magnetic properties of granular perpendicular recording media by using a fcc nonmagnetic intermediate layer with stacking faults

Abstract: Various binary systems are investigated as face-centered cubic (fcc) bases for the nonmagnetic intermediate layer (NMIL) in granular perpendicular recording media. Loss of stacking order on the (111) plane in fcc NMIL is found to enhance the perpendicular magnetic anisotropy energy (KuRL) of the overlying medium. One persuasive reason for this enhancement is the preferred epitaxial growth of magnetic grains on only the (111) atomic terrace of the fcc NMIL due to collapse of the sixfold symmetry of (1¯11), (11¯… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…After many trials for material development, we found that uniaxial crystallographic symmetry is an essential requirement for NMIL materials due to promotion of preferred epitaxial growth of magnetic grains in a granular RL [3]. Fig.…”
Section: Suppression Of Variant Growth Of Magnetic Grains For Granulamentioning
confidence: 98%
See 1 more Smart Citation
“…After many trials for material development, we found that uniaxial crystallographic symmetry is an essential requirement for NMIL materials due to promotion of preferred epitaxial growth of magnetic grains in a granular RL [3]. Fig.…”
Section: Suppression Of Variant Growth Of Magnetic Grains For Granulamentioning
confidence: 98%
“…), addition of the bcc metal former (Cr, Mo, W, Ti, Nb, etc.) into the host fcc material is quite effective [3,4]. Fig.…”
Section: Pseudo-hcp Structure: Fcc Structure With Stacking Faults Formentioning
confidence: 99%
“…The modification of stacking sequence of the close-packed planes from ABCABC to ABABAB could be a result of periodically distributed stacking faults. Similar results have been observed in buffer layers in Co-Cr-Pt magnetic media [16,17], which modify the stacking sequence of fcc into a pseudo-hcp phase [13]. The peaks were separately fitted by pseudo-Voigt fitting and the volume fraction of the pseudo-hcp component was estimated [18] to be around 7.1% for the 10 nm-thick film and 13.6% for t = 5 nm.…”
Section: Resultsmentioning
confidence: 53%
“…This anomalous sputtering process condition leads to some chemical instability (low density of the film) and increased roughness on the top surface of the disk [44]. Therefore, in order to further improve these granular media for high density recording, several key technical issues need to be established, including (1) self-organized nano-dot array formation as a template for the recording layer by a sputtering process, (2) nano-granular thin film formation (recording layer) onto nano-dot arrays used as templates, and (3) development of alternative materials to Ru from the view point of mineral resources [45][46][47].…”
Section: Future Perspectivesmentioning
confidence: 99%